2005
DOI: 10.1677/joe.1.05821
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone regulates the expression of hepatocyte nuclear factor-3 gamma and other liver-enriched transcription factors in the bovine liver

Abstract: Growth hormone (GH) regulates the expression of many genes in the liver, and for some genes this regulation may be mediated through liver-enriched transcription factors (LETFs). As part of the long-term goal to investigate the role of LETFs in GH regulation of gene expression in the liver, in this study we determined the effect of GH administration on the expression of 10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 46 publications
(57 reference statements)
1
23
0
Order By: Relevance
“…It has been shown with conflicting results that the expression of C/EBPa mRNA in mammals is regulated by GH (Vidal et al 1997, Rastegar et al 2000a,b, Strand et al 2000, Eleswarapu & Jiang 2005. In our study, we showed that, although the expressions of C/EBPa in the rainbow trout liver and in RTH cells are not responsive to induction by GH, the level of C/EBPa mRNA decreased in adult fish at 6 h post GH injection.…”
Section: Discussionsupporting
confidence: 40%
“…It has been shown with conflicting results that the expression of C/EBPa mRNA in mammals is regulated by GH (Vidal et al 1997, Rastegar et al 2000a,b, Strand et al 2000, Eleswarapu & Jiang 2005. In our study, we showed that, although the expressions of C/EBPa in the rainbow trout liver and in RTH cells are not responsive to induction by GH, the level of C/EBPa mRNA decreased in adult fish at 6 h post GH injection.…”
Section: Discussionsupporting
confidence: 40%
“…on d0, d7, d56, and d63). The liver biopsy was performed as described previously (Eleswarapu & Jiang 2005). Blood samples were allowed to clot, and were centrifuged to separate the serum.…”
Section: Animals Treatments and Sample Collectionmentioning
confidence: 99%
“…The PCR was run on an Applied Biosystems 7300 Real-Time PCR System (Applied Biosystems) under the following conditions: 50 8C for 2 min, 95 8C for 10 min, and 40 cycles of 95 8C for 15 s and 60 8C for 1 min. The PCR data were analyzed using GAPDH mRNA as an internal control, the expression of which in bovine liver is not affected by nutritional level or GH treatment based on our previous studies (Wang et al 2003, Eleswarapu & Jiang 2005.…”
Section: Real-time Reverse Transcription-pcrmentioning
confidence: 99%
“…Circadian oscillation in plasma glucose, nonesterified fatty acids, b-hydroxybutyrate and urea nitrogen have also been observed in cows (Bitman et al, 1990;Lefcourt et al, 1999). Studies carried out at the molecular level revealed that DBP mRNA expression, a clock-regulated transcription factor that directs hepatocyte metabolism (Oishi et al, 2000;Noshiro et al, 2007), showed a circadian pattern that was altered when cattle were injected with somatotropin (Eleswarapu and Jiang, 2005). These daily cycles in hormones and metabolites likely help coordinate timing of intake with metabolism.…”
mentioning
confidence: 99%